The Local Government Commitment on The Implementation of Social Welfare - Kissumi Diyanayati; Retnaningdyah Weningtyastuti (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2017)
The law No 11 2009 on social welfare states that the implementation of social welfare is shared responsibility between the government, local government and communities. The central government, in this case, is the ministry of social affairs as facilitator and framers policy, while local governments responsibility for social welfare implementation in its respective area by involving participation of the communit, including the business world. The commitment of the local government on residents welfare is the major key of the social welfare, manifested through various activity programs on social services, covering protection and social insurance, social assistance and rehabilitation, and community empowerment. The research took place in East Belitung Regency, with a descriptive qualitative approach. Data gathered from informants which consisted a head of social agency, two sub heads of social agency, two section heads of on social affairs , labor and transmigration, two of the bappeda as head and head of , and a of social institutions (BAZ). Data collected analyzed qualitatively model miles and huberman. Research locations have firm commitment in social welfare agency, two head and sub head of social, men power, and transmigration agency, two heads of development planning agency, and one from local social institution (BAZ). Data are analyzed through qualitative-descriptive technique, through Miles and Huberman model. The local goverment and community in the research location on social welfare handling, proven by decreasing number of pre prosperous 3.208 families (>30 persen) in 2014 to 1.030 familes (12.16 persen) in 2015, within one year term had been an increase in social welfare of 2.178 families.The increase of residents social welfare of Belitung Timurmanifested through various activity programs, among the programs which were touted was renovation of not-habitable houses with budget allocation 45 to 55 million per unit and â€œpelangiâ€ family programs (family hope program) funded by local budget allocation. All people in this district received health insurance (BPJS) through the routine fund receiver (PBI) funded by the national and regional budgets.